Estimación de emisiones de gases por incendios forestales ocurridos en Chimborazo en el período 2016-2019, utilizando sensores remotos - Aguirre Pulla, Mishell Alexandra (2021)
On a global scale, the significant increase in forest fires' recurrence, intensity, and extent has had consequences such as erosion and desertification. On the other hand, the combustion of biomass releases greenhouse gases (GHG) into the atmosphere, which could impact the modification of current climate patterns. In the present work, Seiler and Crutzen (1980) considered the methodological proposal to estimate greenhouse gases produced by forest fires based on auxiliary information from similar reliable studies and remote sensing data. Results derived from the methodology indicated that within Chimborazo province, during the years 2016 to 2019, a biomass content consumed per unit of the burned area of approximately 129 496.30 tons is reported. Representing 16% of affectation due to forest fires concerning the total size of the study area (≅ 650000 ha), registering an entire GHG emissions product of forest fires of 0.1421 of CO2, 0.0088 of CO, 0.0003 of CH4 in teragrams (Tg), identifying 2018 as the year that registers the highest number of GHG emissions for the other years